Electro-optic properties of indium/erbium-codoped lithium niobate crystal for integrated optics. (February 2017) - Du, Wan-Ying; Zhang, Zi-Bo; Ren, Shuai; Wong, Wing-Han; Yu, Dao-Yin; Pun, Edwin Yue-Bun; Zhang, De-Long
Abstract: Clamped and unclamped electro-optic coefficients γ13 and γ33 of In 3+ /Er 3+ -codoped LiNbO3 crystals, which were grown by Czochralski method from the melts containing 0.5 mol% Er2 O3 while varied In2 O3 contents of 0.0, 0.5, 1.0 and 1.5 mol%, were measured by Mach-Zehnder interferometry. The results show that In 3+ /Er 3+ codoping does not cause change of γ13 and γ33, and both γ13 and γ33 can be regarded as unchanged in the studied In 3+ concentration range of 0–2.6 mol% (in crystal) within the experimental error of 3%. The small doping effect is desired in light of the electro-optic application of the crystal. A qualitative, comprehensible explanation for the small effect is given on the basis of the EO coefficient model of LiNbO3 and doping effect on the defect structure of LiNbO3 . Graphical abstract: Electro-optic (EO) property of In 3+ /Er 3+ -doped LiNbO3 crystal has been studied. The results show that In 3+ /Er 3+ codoping does not cause change of clamped and unclamped EO coefficients γ13 and γ33, and the coefficient can be regarded as identical in the studied In 3+ concentration range of 0–2.6 mol% (in crystal) within the experimental error of 3%. The little doping effect is desired in light of the electro-optic application of the crystal. A qualitative, comprehensible explanation for the little effect is given on the basis of the EO coefficient model of LiNbO3 and doping effect on the defect structure of LiNbO3 . Highlights: Electro-optic (EO) property of In 3+ /Er 3+ -doped LiNbO3 (LN) crystal is studied. In 3+ /Er 3+ codoping has small effect on the EO property of LN. The small effect is desired from the viewpoint of the electro-optic application. The small effect is explained in terms of EO coefficient and defect models of LN.